Host and body site-specific adaptation of Lactobacillus crispatus genomes. Issue 1 (24th January 2020) - Pan, Meichen; Hidalgo-Cantabrana, Claudio; Barrangou, Rodolphe
Abstract: Lactobacillus crispatus is a common inhabitant of both healthy poultry gut and human vaginal tract, and the absence of this species has been associated with a higher risk of developing infectious diseases. In this study, we analyzed 105 L. crispatus genomes isolated from a variety of ecological niches, including the human vaginal tract, human gut, chicken gut and turkey gut, to shed light on the genetic and functional features that drive evolution and adaptation of this important species. We performed in silico analyses to identify the pan and core genomes of L. crispatus, and to reveal the genomic differences and similarities associated with their origins of isolation. Our results demonstrated that, although a significant portion of the genomic content is conserved, human and poultry L. crispatus isolates evolved to encompass different genomic features (e.g. carbohydrate usage, CRISPR–Cas immune systems, prophage occurrence) in order to thrive in different environmental niches. We also observed that chicken and turkey L. crispatus isolates can be differentiated based on their genomic information, suggesting significant differences may exist between these two poultry gut niches. These results provide insights into host and niche-specific adaptation patterns in species of human and animal importance.